Mixed methods social network analysis to drive organizational development - Palonen Tuire; Froehlich Dominik E. (Routledge, 2022)
In this volume, mixed methods social network analysis (MMSNA) is mainly discussed as a powerful framework for generating scientific insight. In this chapter, we aim to add a different facet to the discussion by emphasizing MMSNA’s usefulness to inform organizational decision-making and consultancy. Specifically, we give three examples of consultative approaches using MMSNA that deal with themes of leadership, organizational change, and innovation. We discuss the possibilities and limitations of this method of consulting.
Mixed Methods Social Network Analysis : Theories and Methodologies in Learning and Education